2020
DOI: 10.46666/2020.2708-9991.09
|View full text |Cite
|
Sign up to set email alerts
|

Public-Private Partnership in Agricultural Sector of the Republic of Kazakhstan

Abstract: АӨК-де мемлекеттік-жекешелік әріптестік тетіктерін жетілдіру бойынша теориялық тәсілдерді зерделеу және ұсынымдарды негіздеу мемлекет пен бизнес үшін өзара тиімділік жағдайында ауыл шаруашылығы өндірісінің ресурстық базасын кеңейтуге мүмкіндік беретін олардың қажеттілігі мен практикалық маңыздылығымен түсіндіріледі. Қазақстан Республикасының Ауыл шаруашылығы саласында мемлекеттік-жекешелік әріптестікті пайдалану проблемалары талданып, оның агроөнеркәсіптік кешеннің бәсекеге қабілеттілігін арттыру қажеттілігі к… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Zhangirova (2020), this is due primarily to the weak technical equipment of the industry and the lack of innovative approaches in Kazakh animal husbandry. A similar opinion is held by R.K. Konuspayev et al (2020). Therefore, in the analytical review of the state of livestock breeding and the prospects for its development in the near future, it is necessary to consider the possibility of intensification of one or another branch.…”
Section: Introductionmentioning
confidence: 79%
“…Zhangirova (2020), this is due primarily to the weak technical equipment of the industry and the lack of innovative approaches in Kazakh animal husbandry. A similar opinion is held by R.K. Konuspayev et al (2020). Therefore, in the analytical review of the state of livestock breeding and the prospects for its development in the near future, it is necessary to consider the possibility of intensification of one or another branch.…”
Section: Introductionmentioning
confidence: 79%
“…In some additional studies, authors found a positive relationship between the introduction of digital technologies and productivity and efficiency in agriculture production. The introduction of new technology contributes to the simplification of procedures, the supervision and certification of agricultural products and the growth of productivity [6]. The implementation of production functions in the economic analysis of the processes of companies and individuals in the agricultural industry is demonstrated through scientific research conducted in the twenty-first century.…”
Section: Literature Reviewmentioning
confidence: 99%